Achieving Blue Economy goals by implementing digital technologies in the maritime transport sector - Tijan, Edvard (Array, 2021)
This paper analyses how digital technologies implementation in the maritime transport sector companies can help in achieving the Blue Economy goals. Previous research offering a comprehensive overview of digital technologies in the maritime transport sector within the context of the Blue Economy is scarce. To fill this research gap, the economic effects of maritime transport are investigated, and the positive impacts of digital technologies on maritime transport are analyzed, all in the context of the Blue Economy. The authors have concluded that by implementing digital technologies in the maritime transport sector, the Blue Economy goals related to maritime transport (for example transport cost reduction, decreased harmful emissions generated during the voyage and at the berth) can better be achieved, etc.